2019
DOI: 10.3390/app10010040
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Wilms’ Tumor 1 Protein in Human Tissues: From Ontogenesis to Neoplastic Tissues

Abstract: The human Wilms’ tumor gene (WT1) was originally isolated in a Wilms’ tumor of the kidney as a tumor suppressor gene. Numerous isoforms of WT1, by combination of alternative translational start sites, alternative RNA splicing and RNA editing, have been well documented. During human ontogenesis, according to the antibodies used, anti-C or N-terminus WT1 protein, nuclear expression can be frequently obtained in numerous tissues, including metanephric and mesonephric glomeruli, and mesothelial and sub-mesothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 149 publications
(231 reference statements)
4
15
0
Order By: Relevance
“…This cellular localization had been described in preceding reports (Hashiba et al, 2007;Schittenhelm et al, 2008;Bassam et al, 2014;Rauscher et al, 2014;Kusum and Ramita;Lee et al, 2019). In fact, WT1 is a nuclear/cytoplasmic shuttling protein that transports with polysomes, and a substantial part of WT1 protein localizes in the cytoplasm (Salvatorelli et al, 2020). Our finding, conform with the datum that WT1 is involved in RNA metabolism beside its role as a transcription factor, additionally, overexpression of WT1 isoforms lacking a nuclear localization signal was proposed (Bassam et al, 2014;Lee et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This cellular localization had been described in preceding reports (Hashiba et al, 2007;Schittenhelm et al, 2008;Bassam et al, 2014;Rauscher et al, 2014;Kusum and Ramita;Lee et al, 2019). In fact, WT1 is a nuclear/cytoplasmic shuttling protein that transports with polysomes, and a substantial part of WT1 protein localizes in the cytoplasm (Salvatorelli et al, 2020). Our finding, conform with the datum that WT1 is involved in RNA metabolism beside its role as a transcription factor, additionally, overexpression of WT1 isoforms lacking a nuclear localization signal was proposed (Bassam et al, 2014;Lee et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…Using IHC antibodies against C-terminal, WT1 expression was thought to be exclusively nuclear. Upon the development of antibodies against N-terminal (clone WT6F-H2), it became logical to detect WT1 in the cytoplasm, or concurrently in the nucleus and cytoplasm (Salvatorelli et al, 2020). Among our samples, WT1 was detected in the cytoplasm, astrocytic processes and fibrillary tumor matrix with infrequently, concomitant nuclear expression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, WT1 cytoplasmic immunostaining has also been documented in endothelial cells of most benign and malignant vascular tumors [ 35 , 36 ] in juvenile-type fibromatoses, infantile/congential fibrosarcomas, rhabdomyosarcomas, some neuroblastic tumors, some benign and malignant peripheral nerve sheath tumors, gastrointestinal stromal tumors (GIST), leiomyosarcomas, epithelioid cell myofibroblastomas of the breast, and in rhabdomyosarcoma [ 37 , 38 , 39 ], a tumor composed of malignant mesenchymal cells showing morphological, immunohistochemical, and ultrastructural features of skeletal muscle differentiation. These findings seem to support the hypothesis that not only nuclear but also WT1 cytoplasmic expression in some tumors recapitulates that observed during normal development [ 33 , 34 ]. Based on these findings obtained in both developmental and neoplastic tissues, it has been suggested that WT1 is a reliable marker of both endothelial and skeletal muscle differentiation [ 33 , 34 ].…”
Section: Introductionsupporting
confidence: 88%
“…However, there is increasing evidence that the latter staining truly reflects the presence of the protein within the cytoplasm, suggesting its complex regulator activity in transcriptional/translational processes [ 30 , 31 , 32 ]. Recently, we showed that WT1 is also diffusely expressed in the cytoplasm of human fetal endothelial and skeletal muscle cells, as well as in developing sympathetic neuroblasts [ 33 , 34 ]. Interestingly, WT1 cytoplasmic immunostaining has also been documented in endothelial cells of most benign and malignant vascular tumors [ 35 , 36 ] in juvenile-type fibromatoses, infantile/congential fibrosarcomas, rhabdomyosarcomas, some neuroblastic tumors, some benign and malignant peripheral nerve sheath tumors, gastrointestinal stromal tumors (GIST), leiomyosarcomas, epithelioid cell myofibroblastomas of the breast, and in rhabdomyosarcoma [ 37 , 38 , 39 ], a tumor composed of malignant mesenchymal cells showing morphological, immunohistochemical, and ultrastructural features of skeletal muscle differentiation.…”
Section: Introductionmentioning
confidence: 99%